Technology-Enabled Innovations in Education Select Proceedings of CIIE 2020 - Hosseini, Samira; Peluffo, Diego Hernan; Nganji, Julius; Arrona-Palacios, Arturo (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book contains peer-reviewed selected papers of the 7th International Conference on Educational Innovation (CIIE 2020). It presents excellent educational practices and technologies complemented by various innovative approaches that enhance educational outcomes. In line with the Sustainable Development Goal 4 of UNESCO in the 2030 agenda, CIIE 2020 has attempted to "ensure inclusive and equitable quality education and promote lifelong learning opportunities for all." The CIIE 2020 proceeding offers diverse dissemination of innovations, knowledge, and lessons learned to familiarize readership with new pedagogical-oriented, technology-driven educational strategies along with their applications to emphasize their impact on a large spectrum of stakeholders including students, teachers and professors, administrators, policymakers, entrepreneurs, governments, international organizations, and NGOs.
Natural Language Processing for Video Essays and Podcasts in Engineering -- Action Research as a Way to Guide Research Projects in Engineering -- A Contrast-Pattern Characterization of Web Site Visitors in Terms of Conversions -- Massive-Flexible Digital Courses During COVID-19 Pandemic: From Course Structure to Enabling Tools -- Design of a Novel High School Mathematics Class Through the Usability Analysis of a Robot Implementation.
Keywords: Application software; Education-Data processing; Computer vision; Computer and Information Systems Applications; Computers and Education; Computer Vision